2018
DOI: 10.1002/adma.201800764
|View full text |Cite
|
Sign up to set email alerts
|

Room‐Temperature Triple‐Ligand Surface Engineering Synergistically Boosts Ink Stability, Recombination Dynamics, and Charge Injection toward EQE‐11.6% Perovskite QLEDs

Abstract: Developing low-cost and high-quality quantum dots (QDs) or nanocrystals (NCs) and their corresponding efficient light-emitting diodes (LEDs) is crucial for the next-generation ultra-high-definition flexible displays. Here, there is a report on a room-temperature triple-ligand surface engineering strategy to play the synergistic role of short ligands of tetraoctylammonium bromide (TOAB), didodecyldimethylammonium bromide (DDAB), and octanoic acid (OTAc) toward "ideal" perovskite QDs with a high photoluminescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
373
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 475 publications
(384 citation statements)
references
References 48 publications
10
373
1
Order By: Relevance
“…An absolute PLQY of 9.36% was also observed under 360 nm excitation. [43,44] As for the white-emission perovskite QDs, combinations of a self-trapped excitons associated with the octahedra distortion upon irritation were responsible for the photoluminescence mechanism. A representative two-photon luminescence spectrum of the MQDs is shown in Figure 3b, and is similar to the single-photon fluorescence spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…An absolute PLQY of 9.36% was also observed under 360 nm excitation. [43,44] As for the white-emission perovskite QDs, combinations of a self-trapped excitons associated with the octahedra distortion upon irritation were responsible for the photoluminescence mechanism. A representative two-photon luminescence spectrum of the MQDs is shown in Figure 3b, and is similar to the single-photon fluorescence spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Zhong's group used a method combining multiple phases (DMF as “aqueous phase,” n‐hexane as “oil phase,” OA as “surfactant,” and tert‐butanol as demulsifier) to synthesize MAPbBr 3 colloidal QDs by adding a certain amount of tert‐butanol into the DMF solution to form a suspension and then centrifuged and dissolved them in toluene. This method could better control the size of the as‐prepared QDs from 2 to 8 nm and achieved high PL QYs of 80%‐92% . Brabec et al utilized chloroform as an antisolvent to synthesize FAPbX 3 NCs .…”
Section: Synthesis Of Perovskite Ncsmentioning
confidence: 99%
“…In recent years, all‐inorganic CsPbX 3 (X = Br, Cl, or I) nanoacrystals (NCs) have shown great potential for the next‐generation lighting and display applications due to their low material cost, high defect tolerance, tunable emission wavelength with narrow bandwidth, and high photoluminescence quantum yield (PLQY) . The external quantum efficiency (EQE) of light‐emitting diodes (LEDs) incorporating CsPbX 3 NCs as the active layer has increased abruptly from 0.12% to 11.6% in the last 3 years.…”
Section: Introductionmentioning
confidence: 99%
“…Those ligands that remain on the surface of CsPbX 3 NCs have been identified as playing a crucial role in determining the device performance of LEDs . For example, Sargent and co‐workers prepared CsPbX 3 quantum dots (QDs) capped with a relatively short ligand, namely didodecyl dimethyl ammonium bromide (DDAB) and found that DDAB resulted in efficient charge injection and better charge transport.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation